Regulations for and against cooperation in smallcells: How could regulations stimulate co-opetition by supporting sharing? - Amirhossein Ghanbari; Jan Markendahl; Ashraf Awadelakrim Widaa (International Telecommunications Society (ITS), 2013)
Cooperation between Mobile Network Operators (MNO), as competing entities, has become a solution to overcome lack of revenue by reducing expenditures during recent years; where theses cooperation patterns consist of horizontal and vertical models. As much as all these models apply in macrocell networks, they are all applicable in smallcell networks as well, but it is observed that smallcells are still deployed in single operator patterns. On the other hand, telecom regulatory authorities are always concerned about cooperation between operators since they prefer fare distribution of market power among competing operators. The idea to stimulate competition, in order to bring maximum profit for end users, is an ultimate goal for regulators. At the same time, regulators are worried if a high level of collaboration between operators introduces new dilemmas such as creating closed clubs with significant market power. In this paper we first discuss interpretations of national European telecom regulators from the European electronic communications regulatory framework, which is considered as a reference for all countries. Surprisingly, we see that European countries have different interpretations of the same European framework while transposing it into their regulations. Next, the effect of these regulations that are either pro or against cooperation in smallcell networks is investigated. We conclude by presenting the idea that European regulators may need to revise their legislations by considering regulation for promoting smallcell wholesale network sharing as the proper solution.
Keywords: 330